2016
DOI: 10.1016/j.seppur.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biofoulants illustrates different membrane fouling mechanisms for aerobic and anaerobic membrane bioreactors

Abstract: Please cite this article as: Y. Xiong, M. Harb, P-Y. Hong, Characterization of biofoulants illustrates different membrane fouling mechanisms for aerobic and anaerobic membrane bioreactors, Separation and Purification Technology (2015), doi: http://dx.doi.org/10.1016/j.seppur. 2015.11.024 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 61 publications
(63 reference statements)
5
24
0
Order By: Relevance
“…The finding of SMP containing lower 100 kDa in our study was consistent with past studies [25,32], in which by using HPSEC-UV detector and RID, they have reported that these substances can be proteins, polysaccharides, humics. The EPS of cake layers contained large MW than the SMP and their MW distribution ranged from to 450 kDa to over 1,100 kDa which was consistent with previous studies, ranging 488 − 3,397 kDa [25]. Especially Xiong et al [25] found that the peak of 488 kDa substances in cake layers gradually shift to 838 kDa in a longer-filtration operation.…”
Section: Molecular Weight Distribution Of Eps Fractionssupporting
confidence: 93%
See 2 more Smart Citations
“…The finding of SMP containing lower 100 kDa in our study was consistent with past studies [25,32], in which by using HPSEC-UV detector and RID, they have reported that these substances can be proteins, polysaccharides, humics. The EPS of cake layers contained large MW than the SMP and their MW distribution ranged from to 450 kDa to over 1,100 kDa which was consistent with previous studies, ranging 488 − 3,397 kDa [25]. Especially Xiong et al [25] found that the peak of 488 kDa substances in cake layers gradually shift to 838 kDa in a longer-filtration operation.…”
Section: Molecular Weight Distribution Of Eps Fractionssupporting
confidence: 93%
“…The EPS of cake layers contained large MW than the SMP and their MW distribution ranged from to 450 kDa to over 1,100 kDa which was consistent with previous studies, ranging 488 − 3,397 kDa [25]. Especially Xiong et al [25] found that the peak of 488 kDa substances in cake layers gradually shift to 838 kDa in a longer-filtration operation. This finding is consistent with the phenomena of the larger MW of cake layers than bulk sludge in our study.…”
Section: Molecular Weight Distribution Of Eps Fractionssupporting
confidence: 86%
See 1 more Smart Citation
“…Comparative research of Xiong et al [29] on the membrane fouling mechanisms of aerobic (AeMBR) and anaerobic membrane bioreactors (AnMBR) showed faster membrane fouling in the AeMBR system. Also the fouling mechanisms in AeMBR and AnMBR systems are different, therefore fouling control strategies for these two systems should be different [29].…”
Section: Membrane Foulingmentioning
confidence: 97%
“…In addition to reiterating the potential for variability among pathogenic species, these results also accentuate the potential for improved pathogen removal rates by anaerobic MBRs. Although the reason for observed higher LRVs by anaerobic MBRs is not clear due to the limited number of studies addressing this issue, one potential explanation could be associated with differences in membrane fouling mechanisms observed in aerobic and anaerobic MBRs [124]. These differences are potentially significant given recent observations that membrane biofilms can improve bacterial LRVs and effluent water quality in general [125].…”
Section: Pathogen-associated Risk Reduction By Membrane Bioreactorsmentioning
confidence: 99%